The Synthesis, Antimicrobial Activity, and Molecular Docking of New 1, 2, 4-Triazole, 1, 2, 4-Triazepine, Quinoline, and Pyrimidine Scaffolds Condensed to Naturally Occurring Furochromones - Ameen Ali Abu-Hashem; Sami A. Al-Hussain (MDPI AG, 2022)
This study aims to synthesize a new series of furochromone derivatives, evaluate their antimicrobial properties, and improve the permeability of potent compounds to inhibit different types of bacteria and fungi. Hence, Substituted furo[3,2-g]chromene-6-carbonitrile (3a,b) readily form 7-amino-5-methyl-furo [3,2-g]chromene-6-carbonitrile (4a,b) via reduction using sodium borohydride in methanol. The same compounds of (4a,b) were used as starting materials for the synthesis of new furochromone derivatives such as furochromeno [2,3-d]pyrimidines, N- (6-cyano- 5-methyl-furochromene) acetamide, N-(6-cyano-5-methyl-furo chromene)-2-phenyl acetamide, N- (6-cyano-5-methyl-furochromene) formimidate, furochromeno[1,2,4]triazepin-5-amine, furochrom ene-6-carboxamide, furochromeno[1,2,4]triazolopyrimidines, and furochromeno[2,3-b]quinolin- 6-amine. The structures of the new compounds were determined using spectroscopy: Nuclear Magnetic Resonance (1H, 13C), Mass spectra, Infrared, and elemental analysis. Molecular docking studies were conducted to investigate the binding patterns of the prepared compounds against DNA-gyrase (PDB 1HNJ). The results displayed that compounds furochromenotriazolopyrimidine (20a,b), furochromenoquinolin-6-amine (21a,b), furochromenotriazepin-amine (9a,b), and furo- chromenopyrimidine-amine (19a,b) were excellent antimicrobials.